STRATEGI PEMBELAJARAN MENDALAM (DEEP LEARNING) DAN METODE IMPLEMENTASINYA PADA PENDIDIKAN DASAR: A SYSTEMATIC LITERATURE REVIEW - Irwan, Alken; Efendi, Rendi Nur; Tohamba, Citra Prasiska Puspita; Fahmi, Fahmi; Aswita, Dian (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
Deep learning in elementary education has become increasingly relevant as 21st-century competencies emphasize conceptual understanding, transferability, and higher-order thinking skills from an early stage. This study aimed to synthesize deep learning strategies and their implementation methods in elementary education using a systematic literature review (SLR) approach based on PRISMA. The search process was conducted using keywords related to “deep learning” and “elementary education” across national and international academic databases, followed by screening based on inclusion–exclusion criteria and data extraction for thematic synthesis. Of the 30 documents identified, 20 studies met the criteria for analysis. The findings indicate that deep learning in elementary education is most commonly operationalized through project-based, problem-based, and inquiry-based strategies, strengthened by collaboration and reflection as cross-cutting elements. Recurring implementation patterns include contextual engagement, exploration, concept reinforcement, product or solution creation, presentation and feedback, and reflection, with authentic assessment (performance rubrics, portfolios, and self/peer assessment) ensuring learning depth. The most consistent impacts include improved conceptual understanding, enhanced critical thinking and problem-solving skills, and the development of communication and collaboration abilities. These findings highlight the importance of strengthening teachers’ capacity in designing tasks and authentic assessments, as well as providing institutional support to ensure sustainable implementation of deep learning in elementary education.